Involved ethnography in the study of embodied agency – Capturing movement that evades the eye - Satama S; Laurila J (My University, 2022)
<!--[if gte mso 9]> <![endif]-->
Providing understanding on the micro-level foundation of the activities of organizations is dependent on ethnographic approaches (see e.g. Desmond 2007; Kellogg 2009; Michel 2011; Nippert-Eng 1996; Wulff 2001). While these approaches contain several variations of one general theme, there is still room for a form of ethnographic research that we have named involved ethnography. In this approach, the researcher is more involved with the social community being studied than a typical ethnographer, but less involved of that than an actual member of the same community. In addition, involved ethnography takes into account and builds on the process in which a researcher may during the fieldwork turn from an outsider into an active partaker in relation to the community being studied. We believe that this form of ethnography is an especially critical tool in the examination of the subtle variations in how organizational routines are being implemented. To support our argument, we present observations from an ongoing study on professional dance. In this context, variation in micro-level organizational routines materializes in the form of embodied agency as a substantial part of dancers’ work consists of shaping routines through the means of bodily and aesthetic expression. In its entirety, the study makes two main contributions. First, it operates as an example of how involved ethnography is conducted in practice and thus permits us to define the most distinctive characteristics of this approach. Second, it provides general insight into the kinds of conceptual phenomena that can be addressed with this particular form of ethnography.
<!--[if gte mso 9]> Normal 0 21 false false false FI X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} --> <!--[endif] -->
European Group for Organizational Studies (EGOS)